Importance of Conventional Radiography in Diagnosis and Management of Giant Cell Tumour at an unusual location - Jilowa, Sarita; Verma, GC; Sharma, BB; Singh, Jitendra; Singh, Yashvant; Mishra, RK; Bhardwaj, Atul (Indian Journal of Case Reports, 2015)
Giant cell tumour (GCT) or osteoclastoma of the bone is mostly benign but locally aggressive primary tumour of unknownorigin occurring at epiphysis. It is a tumour of long bones and rarely seen in bones of hand and foot. The cases are reported in tarsal and carpal bone but involvement of metatarsal bone is very rare. We present a case of twenty years old female patient with GCT of second metatarsal of left foot. The patient underwent aggressive curettage and filling with bone chips and is on regular follow up.